A New Approach for Sensitivity Analysis in Network Flow Problems - Aini, Asghar; Eshghi, Kourosh; Salehipour, Amir (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
This paper proposes a new approach to study the sensitivity analysis in the network ow problems, in particular, the minimum spanning tree and shortest path problems. In a sensitivity analysis, one looks for the amount of changes in the edges’ weights, number of edges or number of vertices such that the optimal solution, i.e. the minimum spanning tree or shortest path does not change. We introduce a novel approach for this purpose, and develop associated mathematics. We discuss two illustrative examples to show the applicability of the proposed approach.